Chaotic dynamics in resonant tunneling optoelectronic voltage controlled oscillators - Romeira, Bruno (2012)
A new way of generating electrical and optical chaotic carriers is demonstrated using an optoelectronic voltage controlled oscillator consisting of a laser diode (LD) driven by a resonant tunneling diode (RTD) perturbed by radio-frequency signals. The high-dimensional broadband (gigahertz-wide) chaotic current produced by the RTD modulates a LD, providing a simple way to convert electrical chaotic signals into optical subcarriers that can be transmitted by conventional optical channels. Since the chaotic current and the chaotic optical subcarriers are controlled accurately and reproducibly by the RTD, we anticipate this concept can be used as the core of a compact, simple, and low-power consumption optical chaos generator for optical communications.